1997
DOI: 10.1002/(sici)1099-1352(199701/02)10:1<26::aid-jmr351>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the bovine α-chymotrypsin:kunitz inhibitor complex. An example of multiple protein:protein recognition sites

Abstract: The crystal structure of bovine alpha-chymotrypsin (alpha-CHT) in complex with the bovine basic pancreatic trypsin inhibitor (BPTI) has been solved and refined at 2.8 A resolution (R-factor = 0.18). The proteinase:inhibitor complex forms a compact dimer (two alpha-CHT and two BPTI molecules), which may be stabilized by surface-bound sulphate ions, in the crystalline state. Each BPTI molecule, at opposite ends, is contacting both proteinase molecules in the dimer, through the reactive site loop and through resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…The bovine pancreatic trypsin inhibitor belongs to the Kunitz-type inhibitors and is a potent inhibitor of serine proteases. The crystal structures of BPTI with bovine trypsin and with bovine chymotrypsin have been determined [47][48][49]. Analysis of these complexes have shown that there are 10-13 residues on the inhibitor forming less than 4 Å contacts with 20-25 residues of the enzyme.…”
Section: Page 7 Of 22mentioning
confidence: 83%
“…The bovine pancreatic trypsin inhibitor belongs to the Kunitz-type inhibitors and is a potent inhibitor of serine proteases. The crystal structures of BPTI with bovine trypsin and with bovine chymotrypsin have been determined [47][48][49]. Analysis of these complexes have shown that there are 10-13 residues on the inhibitor forming less than 4 Å contacts with 20-25 residues of the enzyme.…”
Section: Page 7 Of 22mentioning
confidence: 83%
“…Previously, the cDNA corresponding to AceKI was amplified from adult A. ceylanicum RNA by using a PCR-based approach (48). The translated cDNA suggested that AceKI represents a novel member of the Kunitz family of serine protease inhibitors, which are characterized by six cysteine residues that form three intramolecular disulfide bonds (8,43,44,49). Based on alignment of the AceKI amino acid sequence with the sequences of previously identified members of the Kunitz family, we hypothesized that Met 26 was the likely P1 inhibitory reactive site of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although this interaction is reversible, the enzyme-inhibitor complex is sufficiently stable that considerable inhibition can be detected at nearly equimolar concentrations. Based on an alignment of AceKI with other members of the Kunitz-type family, we identified Met 26 as the likely P1 inhibitory reactive site amino acid (8,43,49,66). Therefore, in order to more clearly elucidate the role of Met 26 in defining the spectrum of inhibition of AceKI, a series of site-directed mutants were produced that had various substitutions incorporated at the P1 site (23,33,41,46,51,65).…”
Section: Vol 72 2004 Hookworm Kunitz Inhibitor 2215mentioning
confidence: 99%
“…The analysis of the crystal structures of bovine trypsin-BPTI [6] and bovine chymotrypsin-BPTI [7][8] complexes shows that there are 13 residues of BPTI forming < 4 Å contacts with the enzyme (Table (1)). Large part of All values were calculated using HBPLUS program [18] and structural data for respective trypsin-BPTI [6] and chymotrypsin-BPTI complexes [8]; in case of Arg15, values were calculated from data for APPI complexed with trypsin or chymotrypsin [8].…”
Section: Accommodation Of the P1 Residues In The S1 Pocket Of Trypsinmentioning
confidence: 99%